PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN NEARPOD UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPS - Fais Arina Zulfa; Ali Imron; Soesanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this writing is to determine the improvement in learning outcomes of class VIII H students at SMP Negeri 3 Surabaya through the Discovery Learning Model assisted by the interactive website, Nearpod. This research was carried out using the collaborative classroom action research (PTK) method with each cycle consisting of four stages, namely Design, Implementation, Observation and Reflection. The results show that the cognitive learning output of students in cycle 1 with an average completeness of 61.76% with sufficient criteria. Meanwhile, in cycle 2, students' learning outcomes had an average completeness of 85.29% with good criteria. So it can be concluded that the application of the Discovery Learning learning model with the help of the interactive website Nearpod can improve the learning outcomes of class VIII H students at SMP Negeri 3 Surabaya.